RETURN SAHAM DENGAN MENGGUNAKAN ANALISA TEKNIKAL MOVING AVERAGE - Yuliaty, Erma; Brahmayanti, Ida Ayu Sri; Trihastuti, Adiati (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2021)
Modern society understands investment. One of the investment options in the capital market that is most in demand by investors is stock securities. There are two types of investors in the capital market: actual investors who invest for the long term and short-term investors (day traders) who invest daily using stock price changes. The analysis used by day traders is called technical analysis. There are various kinds of technical analysis tools, one of which is the Moving Average. On the Moving Average, an indicator can be used to execute a sell called the Death Cross, and a buy execution called the Golden Cross. This study uses the Moving Average indicator to generate investment returns on stocks that have prices above Rp. 10,000 and stocks that have prices below Rp. 10,000. From the results of observations of 9 stocks that have a price above Rp 10,000 and 9 shares with a price below Rp 10,000, it is found that stocks with prices below Rp 10,000 generate an average return of +27.64% while stocks with prices above Rp. IDR 10,000 generates an average return of +10.28%. Meanwhile, the average loss of shares priced above Rp 10,000 is -18.54%, while shares below Rp 10,000 generate an average loss of -9.88%.